CX3CL1/CX3CR1-Mediated Microglia Activation Plays a Detrimental Role in Ischemic Mice Brain via p38MAPK/PKC Pathway. Issue 10 (October 2015) - Liu, Yong; Wu, Xiao-Mei; Luo, Qian-Qian; Huang, Suna; Yang, Qing-Wu Qian; Wang, Fa-Xiang; Ke, Ya; Qian, Zhong-Ming
The exact roles of activated microglia and fractalkine (CX3CL1)/fractalkine receptor (CX3CR1) signaling are not fully understood in brain ischemic injury and the findings reported are controversial. Here, we investigated the effects of CX3CR1 siRNA on the expression of CX3CR1, p38 mitogen-activated protein kinase (p38MAPK), Protein Kinase C (PKC) and inflammatory cytokines, microglia activation, white matter lesions, and cognitive function in mice treated with bilateral common carotid artery stenosis (BCAS) in vivo as well as effects of exogenous CX3CL1, CX3CR1 siRNA, and SB2035080 on expression of inflammatory cytokines in BV2 microglia treated with oxygen–glucose deprivation (OGD) in vitro . We showed that CX3CR1 siRNA significantly inhibited the increased expression of CX3CR1, p38MAPK, PKC as well as tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, and IL-6, and also attenuated microglia activation, white matter lesions, and cognitive deficits induced by BCAS in mice brain. We also showed that exogenous CX3CL1 could induce a further enhancement in TNF-α and IL-1β expression, which could be suppressed by CX3CR1 siRNA or by the p38MAPK inhibitor in OGD-treated BV2 microglial cells in vitro . Our findings indicated that CX3CL1/CX3CR1-mediated microglial activation plays a detrimental role in ischemic brain via p38MAPK/PKC signaling and also suggested that CX3CL1/CX3CR1 axis might be a putative therapeutic target to disrupt the cascade of deleterious events that lead to brain ischemic injury.